Analisis Faktor-Faktor yang Mempengaruhi Produktivitas Budidaya Ikan Nila di Indonesia: Studi Literatur - Karya Haga Mendrofa; Zebua, Estin Krisdila (Zoologi: Jurnal Ilmu Peternakan, Ilmu Perikanan, Ilmu Kedokteran Hewan, 2025)
Tilapia (Oreochromis niloticus) production is very important to maintain food security and the Indonesian fisheries economy. Based on a literature study conducted from 2021 to 2024, this study aims to analyze the components that influence the productivity of tilapia cultivation. The method used is a literature study by reviewing various studies that discuss the technical, environmental, social, and economic aspects of tilapia cultivation. The results of the study indicate that government policies, fish density, feed, and water quality all affect the productivity of tilapia cultivation. In addition, there is evidence that advanced technologies such as biofloc systems and aquaculture transition systems (RAS) improve production efficiency and sustainability. This study provides suggestions for increasing productivity through optimal environmental management, use of appropriate technology, and policy support that supports farmers.